Needs assessment of psychocutaneous medicine amongst dermatology practitioners in South Africa - Mokwatlo, Kaisha (My University, 2022)
Background Studies conducted in high-income countries reported that one in three patients seen at dermatology facilities suffers from an underlying psychological problem. However, the current literature is limited regarding the prevalence in low- and middle income countries or the awareness of psychocutaneous medicine in these settings. This study aims to assess the level of comfort in assessing patients with psychocutaneous conditions, prescribing psychotropic drugs, training needs in managing psychodermatological conditions, and need for psychodermatology clinics amongst dermatology practitioners in South Africa (SA). Methods A cross-sectional survey was conducted amongst dermatology practitioners in SA from 14 January to 14 March 2021. Members of the Dermatological Society of South Africa (DSSA) and Dermatology Registrar Association of South Africa (DRASA) were asked to complete a needs assessment survey questionnaire linked via e-mail. Results A total of 248 surveys were distributed among dermatology practitioners, and 48 were completed. Only four per cent (n=2) reported being very comfortable prescribing antipsychotic medication to patients. Moreover, a high proportion (72,9%; n=35) of the respondents reported not having received sufficient training in identifying patients with psychological problems. Just over half of the practitioners, 52.1 per cent (n=25), expressed interest in attending educational seminars in psychodermatology. Conclusion We found a low level of comfort in prescribing psychotropic drugs, and almost two-thirds of the practitioners reported a need for psychocutaneous medicine teaching during registrar training. We recommend that further studies be done in African countries.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Dermatology to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022